N-terminal pro-brain natriuretic peptide is a strong predictor of mortality in systemic sclerosis. (15th November 2016) - Allanore, Yannick; Komocsi, Andras; Vettori, Serena; Hachulla, Eric; Hunzelmann, Nicolas; Distler, Jörg; Avouac, Jérôme; Gobeaux, Camille; Launay, David; Czirjak, Laszlo; Kahan, André; Meune, Christophe
Abstract: Objectives: Cardiovascular involvement is a major contributor to mortality in systemic sclerosis (SSc). We examined whether N-terminal pro-brain natriuretic peptide (NT-proBNP) is a reliable predictor of mortality in SSc. Methods and results: This multicentre prospective cohort study included 523 patients presenting with SSc, whose mean age was 54 ± 13 years, mean disease duration 8 ± 9 years, and diffuse cutaneous form in 168. Plasma NT-proBNP was measured at baseline and the patients were followed yearly. Overall mortality was measured at 3 years. At baseline, cardiovascular involvement was present in 37 patients, including 17 with pulmonary artery hypertension (PAH) and 20 with a left ventricular ejection fraction (LVEF) < 55%. At 3 years, 32 (7%) patients had died. The median [25th–75th percentile] NT-proBNP concentration was 203 ng/l [129–514] in patients who died within 3 years, versus 88 ng/l [47–167] in survivors ( P < 0.001). NT-proBNP was an independent predictor of 3-years mortality in multivariate analysis ( P = 0.046). The optimal cut-off derived from the ROC curve was 129 ng/l; sensitivity and specificity to predict 3 y mortality were 78.1 and 66.7%. Using the previously recommended 125-ng/l concentration as threshold value, NT-proBNP reliably and independently predicted 3 year mortality, with a sensitivity of 78.1 and a negative predictive value of 97.6%, respectively ( P = 0.006). The consideration of SSc patients without PAH or LVEF < 55% at baseline yielded similar results. Conclusion: NT-proBNP appears as a reliable and independent predictor of mortality in patients with SSc.